FABRIKASI SERAT NANO BERBASIS POLIMER MENGGUNAKAN TEKNOLOGI ELECTROSPINNING - M. Fahrur Rozy Hentihu; Imam Sholahuddin (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2015)
Nano fibers can be fabricated using electrospinning technology using local components at low cost. Electrospinning technology also has advantages to control the morphology, uniformity, porosity and composition of nano fiber by pumping a solution of the gel through the nozzle of a metal-needle high voltage electrified. Based on the results of the research, the general parameters required for the manufacture of electrospinning machine is a resolution rate of spraying the solution (μℓ / min) and the magnitude of the high voltage power source (kV). A human hair is approximately 60 μm size looks larger than the size of the resulting PVA fiber electrospinning machine. These results were confirmed by the results of fiber characterization using the AFM in the area of ​​fiber 50 μm x 50 μm, fiber size in the range of <1 μm are included in the order of 1000 nm. It can be concluded that the electrospinning machine that has been made in this study has been able to create nanometer-scale fibers.